Complex utilisation of ekibastuz brown coal fly ash: Iron & carbon separation and aluminum extraction. (1st May 2019) - Valeev, D.; Kunilova, I.; Alpatov, A.; Mikhailova, A.; Goldberg, M.; Kondratiev, A.
Abstract: Fly ash landfills that accumulate a by-product of coal combustion and gasification represent a permanent threat to the surrounding environment due to many factors (air and water pollution, soil contamination, wildlife poisoning, etc). Moreover, disposed coal fly ash may contain significant amounts of valuable elements that are not extracted and potentially wasted. To improve the above situation, a combined ash treatment process was developed for utilisation of the coal fly ash waste from coal-fired power stations. The ash treatment includes three stages: 1) magnetic separation of an iron-containing fraction, 2) carbon separation by floatation, and 3) extraction of aluminum by the autoclave hydrochloric acid leaching. The lab-scale results of the ash treatment applied to the Ekibastuz brown coal fly ash from the Omsk power stations (Russia) were presented and discussed. The XRD analysis showed that the fly ash consists primarily of quartz, mullite and magnetite. It was found that the magnetic fraction separated at the first stage is enriched in magnetite (over 20 wt %), the carbon content in the concentrate after flotation increases to 27 wt %, and 90–95% of aluminum can be extracted during the autoclave acid leaching. The SEM analysis showed that the magnetite phase is grown on the surface of alumosilicate spheres as ∼1 μm cubic crystals. The effect of the autoclave temperature and exposure time on the Al extraction efficiency was also investigated and analysed in the present paper. The optimal autoclave temperature and exposure time were found to achieve the maximum Al extraction efficiency. It was also found by the SEM microanalysis that further extraction of aluminum is not economically feasible since the remaining Al is evenly surrounded by SiO2 in the fly ash particles. Highlights: A combined treatment is developed to utilize the coal fly ash (CFA). Magnetic separation is used to separate an iron-containing fraction (magnetite). Unburned carbon is separated by flotation using kerosene as the collector. Up to 95% of Al is extracted by the autoclave hydrochloric acid leaching of CFA. Optimal process parameters are determined to achieve maximum performance.